Planting season alters the interference of weeds in the common bean - Tejada, Jorge Luis [UNESP] (2023)
The common bean has social, economic, culinary, and environmental relevance. Considering its low competitive capacity and the intensive use of herbicides, methods such as planting time can help in weed management. To determine the effect of the planting season on controlling weeds affecting common beans, an experiment was conducted during the summer planting and another in winter planting. For that seven incrementing periods were implemented: 0–10, 0–20, 0–30, 0–40, 0–50, 0–60 and 0–80 days after bean emergence with coexistence of weeds and the same periods with control of weeds, which established 14 treatments in four repetitions, under a random block design. Weeds were analyzed using a phytosociological method and their dry mass with yield examined by regression. The non-linear regression analysis determined the pre-interference period (PIP), the critical period for interference prevention (CPIP) and the total interference prevention period (TIP). The relevant species were Nicandra physaloides, Digitaria nuda and Raphanus raphanistrum. The TIP was similar in both planting seasons. The CPIP was 38 and 33 days in summer planting and winter planting, respectively. The PIP had six more days in winter planting compared to summer planting. The higher dry mass in weeds reduced yield by 14.7 % in winter planting, in relation to the summer planting, but the reduction was faster in this season. Winter planting conferred a certain competitive advantage to the crop over some weed species, thus it could be suggested planting common bean in that season.